Perbedaan Perlekatan Biofilm Streptococcus mutans pada Resin Komposit Nanofil Tipe Universal Restortive dan Flowable Restorative - Andi Kurniawan; Ketut Suardita; Nanik Zubaidah (Conservative Dentistry Journal, 2017)
Back Ground: Adherence of  Stretococcus mutans biofilm (S. mutans) to the surface of dental restorative materials is considered an important step in the development of secondary caries and periodontal disease. There are two type of nanofil composite: universal restorative and flowable restorative. That have different characteristic to induce S.mutans biofilm adherent in it surface.  Purpose: The aim of this study was to compare the adherence of S. mutans biofilm to two types of nanofil restorative materials, flowable restorative and universal restorative.. Materials and Methode: 32 disc-shaped specimens (∅ = 5.0 mm / thickness = 2.0 mm) of two types  composite were divided  to 4 groups (n = 8): group 1; universal restorative were immersed in pH cycling solution for 14 days ,group 2; Universal restorative  were  immersed in water for 14 day,group 3: flowable restorative were immersed in pH cycling solution,group 4: flowable restorative were immersed  for 14 days in water .  in day 15 th,  All speciments(n=32) were immersed for 24 hours in artificial saliva.. Streptococcus mutans cells were brought in contact with and grown on the speciments for 48 hours in BHI-B. Bacterial suspension was deposited onto each material and the adhesion of biofilm was evaluated trough optic density (OD) . Optic density   biofilm of S.mutans analyzed using Elissa reader’ Spectrophotometry. Statistical analysis was performed by Kruskall -wallis and Tukey HSD test  (α = 0.05). Result: Adherence of  S.mutans biofilm on flowable restorative (mean OD:1,933, SD: 0,633)  were significantly higher than universal restorative materials (mean OD: 1,240,SD:0,317). (P<0,05) Conclusion: The adherence of S.mutans biofilm on the surface of composites resin nanofil flowable restorative higher than universal restorative.